Association of Electrocardiographic and Imaging Surrogates of Left Ventricular Hypertrophy with Incident Atrial Fibrillation: The Multi-Ethnic Study of Atherosclerosis - Chrispin, Jonathan (2014)
OBJECTIVES: To examine the association between LVH, defined by cardiovascular magnetic resonance (CMR) and electrocardiography (ECG), with incident AF. BACKGROUND: Previous studies of the association between atrial fibrillation (AF) and left ventricular hypertrophy (LVH) were based primarily on echocardiographic measures of LVH. METHODS: The Multi-Ethnic Study of Atherosclerosis (MESA) study enrolled 4942 participants free of clinically recognized cardiovascular disease. Incident AF was based on MESA ascertained hospital discharge ICD codes and Centers for Medicare and Medicaid Services (CMS) inpatient hospital claims. CMR-LVH was defined as left ventricular mass ≥ 95th percentile of the MESA population distribution. Eleven ECG-LVH criteria were assessed. The association of LVH with incident AF was evaluated using multivariable Cox proportional hazards models adjusted for CVD risk factors. RESULTS: During a median follow-up of 6.9 years, 214 incident AF events were documented. Participants with AF were more likely to be older, hypertensive, and overweight. The risk of AF was greater in participants with CMR-derived LVH [Hazard ratio (HR) 2.04, 95% CI 1.15-3.62]. AF was associated with ECG-derived LVH measure of Sokolow-Lyon voltage product after adjusting for CMR-LVH [HR=1.83 (1.06, 3.14), p= 0.02]. The associations with AF for CMR LVH and Sokolow-Lyon voltage product were attenuated when adjusted for CMR LA volumes. CONCLUSION: In a multi-ethnic cohort of participants without clinically detected CVD, both CMR and ECG-derived LVH were associated with incident AF. ECG-LVH showed prognostic significance independent of CMR-LVH. The association was attenuated when adjusted for CMR LA volumes.